(untitled) (Orchid Academia Siraha, 2022)
A communicable disease, caused by a recently detected severe acute respiratory syndrome corona virus2 (SARS-CoV-2), corona virus disease-19 (COVID-19)pandemic is rapidly increasing across the globe, creating range of psychological impact including panic disorder, stress, anxiety and depression. The objective of this paper is to describe the impact of COVID-19 on mental health of students based on anxiety and depression. The study followed descriptive survey design. Total 51 students of class 9 and 10 of Chhinnamasta-3 Saptari were selected for study. Interview schedule that contained items from General Anxiety Disorder-7 scale and Patient Health Questionnaire-9 were used to collect data. Simple descriptive statistics like percentage mean and T test, Pearson’s ‘r’ test and Spearman’s ‘rho’ test were applied to analyse the data. All students had some level of anxiety and depression. There was no significant difference between the mean score of anxiety and depression among boys and girls. It is suggested that psychological counselling should be immediately provided to respondents.